A novel congestion control strategy in DTN. (1st January 2012) - Liu, Qi-Lie; Pan, Ying-Jun; Li, Yun; Zhao, Ling
Delay tolerant networks (DTNs) are wireless networks where disconnections may occur frequently due to node mobility, power outages and propagation phenomena. To achieve date delivery, store-and-forward protocols are used in DTN and routing protocols based on epidemic message dissemination have been proposed, like epidemic routing. Under epidemic routing, messages can be delivered completely between every two nodes if every node buffer is big enough and the communication time is long enough after one node contacts another. But congestion will occur easily at a node if the buffer of this node is limited under epidemic routing in DTN. To solve this problem, a novel congestion control strategy is introduced. The strategy is called N -DC (drop the copying numbers over N ). By using simulations based on a Random Waypoint model, the simulation results proved the improvement of this strategy.